Analysis of Earthquake Mitigation Symbols in the Film Suzume using Roland Barthes’s semiotic approach - Henderson Suherman, Felix; Jiwanda DL, Jatayu; Budiwinarto, Arif (Communication, 2026)
Films serve as crucial mass communication media for conveying messages to audiences. Suzume is an anime film about the journey of Iwato Suzume and Munakata Souta in closing dimensional-gates and preventing Mimizu from causing disasters. This study analyzes earthquake disaster mitigation symbols in the Japanese anime film Suzume using Roland Barthes' semiotic approach by describing the denotative, connotative, and mythical meanings of disaster symbols. This study employed a descriptive qualitative method, utilizing observation and documentation of key film scenes representing disaster mitigation through three layers of meaning: (1) Denotation as the act of closing and locking the dimensional gates, (2) Connotation as efforts to reduce disaster impact through structural and nonstructural mitigation, and (3) Myths related to Japanese cultural beliefs about gates, keys, gods, and Namazu. These symbols emphasize the importance of structural (physical preparation) and non-structural (knowledge-based) mitigation in earthquake management.